Tata Kelola Negara Turki Dalam Menangani Pandemi COVID-19 - Siska Noviyanti (Departemen Ilmu Pemerintahan Fisip Unhas, 2021)
The purpose of this research is to describe the Turkish state governance in handling the COVID-19 pandemic. Policies implemented by the Turkish government in suppressing the spread of coronavirus include restrictions on traveling and lockdowns. Economic and social policies are implemented to protect the welfare of its citizens in the face of a pandemic. The normalization process was announced with a few loose policies but remained in vigilant mode against the spread of COVID-19. The method used in this study is a qualitative type. Based on the research that has been done, it can be concluded that Turkey can act quickly and responsively in preventing the spread of coronavirus and face the COVID-19 pandemic with policies implemented so that mortality rates do not continue to increase and recovery rates continue to increase. The implication of this research for the development of science is as consideration for a country's governance in implementing policies to deal with a situation.